Taxing Large Businesses: Cooperative Compliance in Action - Lotta Björklund Larsen; Lynne Oats (Intereconomics, 2019)
Cooperative compliance represents a shift in thinking for tax administrations, away from a deterrence approach where taxpayers are coerced to comply with tax rules and threatened by audits and penalties, toward a more responsive and collaborative approach.
Keywords: 330